1996
DOI: 10.1046/j.1365-3083.1996.d01-81.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Epitope Recognized by Non‐Specific Cytotoxic Cells: Determination of the Fine Specificity Using Synthetic Peptides

Abstract: NCC recognize a conserved target cell antigen (NKTag) expressed on protozoan parasites and on transformed tumour cells. In the present study, synthetic peptides corresponding to N-terminal, C-terminal and internal NKTag(deduced) amino acid sequences were tested for binding and inhibition of NCC lysis of sensitive target cells. A 20-mer peptide equivalent to amino acids (aa) nos. 55-74 specifically inhibited NCC lysis of human EBV transformed target cells (IM-9). Inhibitory effects were nonreversible and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Immunoprecipitation experiments using mAb5C6 (anti‐NCC antibody) resulted in the identification of a protein of 34 kDa named NCC receptor protein 1 (NCCRP‐1) [97–100]. The engagement of NCCRP‐1 by NKTag was found to be responsible for the recognition and killing of target cells by NCCs [95,96,98,101]. Further analysis, using synthetic peptides to mimic the ligand demonstrated that the ligand‐binding region of NCCRP‐1 was located between amino acids 104 and 119 [102].…”
Section: Cells and Innate Immunity Of Fishmentioning
confidence: 99%
“…Immunoprecipitation experiments using mAb5C6 (anti‐NCC antibody) resulted in the identification of a protein of 34 kDa named NCC receptor protein 1 (NCCRP‐1) [97–100]. The engagement of NCCRP‐1 by NKTag was found to be responsible for the recognition and killing of target cells by NCCs [95,96,98,101]. Further analysis, using synthetic peptides to mimic the ligand demonstrated that the ligand‐binding region of NCCRP‐1 was located between amino acids 104 and 119 [102].…”
Section: Cells and Innate Immunity Of Fishmentioning
confidence: 99%
“…However, the best characterization of this first step was achieved by the finding of the non-specific cytotoxic cell receptor protein-1 (NCCRP-1) by the generation and selection of a monoclonal antibody (5C6) that completely blocked catfish NCC activity (Evans et al, 1988;Jaso-Friedmann et al, 1988. This receptor showed important features: 1) the 5C6 antibody recognizes the NCCs of most studied fish and even the mammalian NK and LAK cells, demonstrating its conservation (Cuesta et al, 2005a;Evans et al, 1988;McKinney & Schmale, 1997); 2) the NCC activity is blocked by the 5C6 antibody (Evans et al, 1988;Iwanowicz et al, 2004;Jaso-Friedmann et al, 1988; 3) the NCCRP-1 is a 32-34 kDa protein found in the membrane of NCCs and binds to a 42 and 46 kDa from the tumor targets and protozoan that they kill, respectively (Evans et al, 1996;Jaso-Friedmann et al, 1997aLester et al, 1994); and 4) it is a type-III membrane protein and its activation led to tyrosine and serine phosphorylation and uses the Jak-STAT signalling pathway (Evans et al, 1999;Jaso-Friedmann et al, 1995. After binding to the target cell, mammalian NKs and fish NCCs share the same killing mechanisms including granule-dependent (release of perforin and granzymes) and granule-independent (Fas/FasL system) (Cuesta et al, 2003a;Hogan et al, 1999;Jaso-Friedmann et al, 2000;Shen et al, 2002).…”
Section: Fish Innate Cytotoxic Cellsmentioning
confidence: 99%
“…A second study determined that catfish NCC were able to bind and kill 50-60% of Tetrahymena pyriformis after 10 h of coincubation (Graves et al, 1985b). Furthermore, NCC binding to xenogeneic tumor cells and Ichthyophthirius multifiliis or Tetrahymena pyriformis parasites shared the same antigen, that in the case of parasites, consist on a 46 kDa (Evans et al, 1998a(Evans et al, , 1996Graves et al, 1985a;Jaso-Friedmann et al, 1997b;Lester et al, 1994). In another study, gilthead seabream specimens were parasitized with the enteric Enteromyxum leei parasite (Cuesta et al, 2006).…”
Section: Cytotoxic Response Against Parasitesmentioning
confidence: 99%
“…These substances (alarmins) are released from damaged cells, they are not microbial ligands, and they are constitutively expressed by many histological cell types throughout the animal. One member of this group (HMGB-1) [7] is secreted by macrophages (among other types of cells) and has been reported to have cytokine-like activities. HMGB-1 also produces promiscuous binding toTLR-4 and receptor for advanced glycation endproducts on epithelial and endothelial cells [8 -11].…”
Section: Introductionmentioning
confidence: 99%